ILC2-mediated immune crosstalk in chronic (vascular) inflammation - Kral, Maria; van der Vorst, Emiel P.C.; Surnov, Alexey; Weber, Christian; Döring, Yvonne (Frontiers in Immunology, 2023)
Crosstalk between innate and adaptive immunity is pivotal for an efficient immune response and to maintain immune homeostasis under steady state conditions. As part of the innate immune system, type 2 innate lymphoid cells (ILC2s) have emerged as new important regulators of tissue homeostasis and repair by fine-tuning innate-adaptive immune cell crosstalk. ILC2s mediate either pro- or anti-inflammatory immune responses in a context dependent manner. Inflammation has proven to be a key driver of atherosclerosis, resembling the key underlying pathophysiology of cardiovascular disease (CVD). Notably, numerous studies point towards an atheroprotective role of ILC2s e.g., by mediating secretion of type-II cytokines (IL-5, IL-13, IL-9). Boosting these protective responses may be suitable for promising future therapy, although these protective cues are currently incompletely understood. Additionally, little is known about the mechanisms by which chemokine/chemokine receptor signaling shapes ILC2 functions in vascular inflammation and atherosclerosis. Hence, this review will focus on the latest findings regarding the protective and chemokine/chemokine receptor guided interplay between ILC2s and other immune cells like T and B cells, dendritic cells and macrophages in atherosclerosis. Further, we will elaborate on potential therapeutic implications which result or could be distilled from the dialogue of ILC2s with cells of the immune system in cardiovascular diseases.